Assessment of the harmonic distortion in residential distribution networks: literature review (2017)
Harmonic distortion in residential distribution networks is increasing due to the penetration of multiple nonlinear loads, including modern technologies such as plug-in electric vehicles and energy efficient lighting (e.g., compact fluorescent and LED lamps). The distributed nature of these loads introduces complexity in the analysis of harmonic propagation. Therefore, more sophisticated tools are needed to investigate this issue, on the basis of formerly established methodologies. This paper presents a literature review on the assessment of the harmonic distortion in residential distribution networks. To that end, bibliographic data of the most representative publications related to the topic were obtained. From these data, a novel citation analysis method was developed to construct a chronologically organized direct citation network. Based on the temporal evolution of the citation network, the aforementioned issue is presented, identifying lines of research and proposed methodologies. From the analysis of the literature review, the stages for modeling and simulating harmonic propagation are identified and described. The principal aspects to be addressed for obtaining an accurate harmonic analysis are also identified and detailed, namely, harmonic interaction, diversity, unbalance, and uncertainty. Finally, main conclusions are highlighted.